Nasal masks for domiciliary positive pressure ventilation: patient usage and complications. - Jones, D. J. (1994)
BACKGROUND--Nasal mask discomfort is a major factor in compliance with treatment by nasal intermittent positive pressure ventilation (NIPPV) and nasal continuous positive airway pressure (CPAP). METHODS--A study of skin complications resulting from mask usage, with particular reference to predisposing factors, was carried out in 66 patients by means of a postal questionnaire. An effective means of managing ulceration at the nasal bridge while continuing therapy is described. RESULTS--Some disruption of treatment due solely to mask discomfort was experienced by 35 patients (53%), consisting of broken skin or open sores in 11 cases (17%). CONCLUSIONS-Although complications resulting from nasal mask usage are common, early identification of patients at risk of developing such complications and appropriate intervention will result in improved patient compliance.